2008
DOI: 10.1111/j.1740-8709.2008.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parenting behaviours predict young adolescents' nutritional intake and body fatness

Abstract: This study investigated whether perceptions of parenting behaviours predict young adolescents' nutritional intake and body fatness. The randomly selected study sample consisted of 106 13-15 years olds from Houston Metropolitan Statistical Area. Parenting style variables were created by cluster analysis and factor analysis. A two-cluster solution for both maternal and paternal parenting style represented authoritative vs. non-authoritative parenting. Two parenting dimension factors derived were maternal/paterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 40 publications
(34 reference statements)
3
59
0
Order By: Relevance
“…Associations between parenting style and child/adolescent weight status have been observed in several cross-sectional studies, suggesting that an authoritative parenting style is related to a lower BMI or normal weight (Berge 2009;Berge et al 2010a;Chen et al 2005;Kim et al 2008;Ventura and Birch 2008). However, nonsignificant results do also exist (Hennessy et al 2010b;Chen et al 2005;Brann and Skinner 2005;Gibson et al 2007).…”
Section: Introductionmentioning
confidence: 73%
“…Associations between parenting style and child/adolescent weight status have been observed in several cross-sectional studies, suggesting that an authoritative parenting style is related to a lower BMI or normal weight (Berge 2009;Berge et al 2010a;Chen et al 2005;Kim et al 2008;Ventura and Birch 2008). However, nonsignificant results do also exist (Hennessy et al 2010b;Chen et al 2005;Brann and Skinner 2005;Gibson et al 2007).…”
Section: Introductionmentioning
confidence: 73%
“…[19, 38] However, this relationship was not found among normal weight children. A relationship between warm parenting was also not found among any aberrant eating behavior in either weight group.…”
Section: Discussionmentioning
confidence: 99%
“…[35, 36] High levels of psychological control have also been associated with higher levels of energy-dense snack consumption. [19] On the other hand, studies have demonstrated that high levels of behavioral control are associated with decreased risk of dieting[37], snacking,[38] and sugar sweetened beverage intake. [19] Most of these studies have been conducted using a general population of American or European children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that perceptions of authoritative parenting were associated with greater physical activity (in girls only). Similarly, only a small number of studies have examined adolescents' perceptions of parenting styles in relation to healthy eating and dietary practices (Kim et al, 2008;Kremers, Brug, de Vries, & Engels, 2003). Nonetheless, a consistent pattern across these studies was that adolescents' perceptions of authoritative parenting were found to be associated with the most adaptive responses.…”
Section: Parenting Stylesmentioning
confidence: 93%